1995
DOI: 10.1002/1097-4679(199505)51:3<340::aid-jclp2270510304>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of antidepressant outcome studies that involved children and adolescents

Abstract: A meta‐analysis was performed of available studies that document response to antidepressant medications in the pediatric population, based upon guidelines developed in a methodological review of adult antidepressant response (Greenberg, Borstein, Greenberg, & Fisher, 1992). The 27 studies accessed through standard medical and psychological data bases were assessed against the following criteria: degree of blindness, placebo group design, rating issues, sample size, inclusion criteria, and other methodological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some site psychiatrists expressed the concern that quiet, depressed children were not being prescribed potentially beneficial medications because such children were less likely to come to the attention of a physician than those with behavior disorders. Alternative explanations may be that clinicians were responding to the lack of evidence regarding the efficacy of antidepressants in adolescents (Ambrosini, Bianchi, Rabinovich, & Elia, 1993a;Ambrosini et al, 1993b;Ryan, 1993;Thurber, Ensign, Punnett, & Welter, 1995) or that nonpharmacological interventions may have been tried more readily and satisfactorily for children with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Some site psychiatrists expressed the concern that quiet, depressed children were not being prescribed potentially beneficial medications because such children were less likely to come to the attention of a physician than those with behavior disorders. Alternative explanations may be that clinicians were responding to the lack of evidence regarding the efficacy of antidepressants in adolescents (Ambrosini, Bianchi, Rabinovich, & Elia, 1993a;Ambrosini et al, 1993b;Ryan, 1993;Thurber, Ensign, Punnett, & Welter, 1995) or that nonpharmacological interventions may have been tried more readily and satisfactorily for children with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the effect size was reported from five studies with dichotomous outcome (improved/not improved) as an odds ratio of 1.08 (95% CI = 0.53-2.17) indicating a similar likelihood of response for the pooled TCA-treated (38.5%) and placebo-treated (37.1%) youths. During the same year, there was a review of 27 outcome studies involving antidepressant treatment (although not restricted to the more rigorous randomized, double-blind, controlled parallel group clinical trial design) [20]. The authors found the studies substantially lacking in each of the criteria for the review, namely 1) the degree of blindedness, 2) placebo-controlled designs, 3) rating scale issues, 4) sample size, 5) inclusion criteria, and 6) other methodologic issues.…”
Section: Randomized Clinical Trials and Gaps In The Evidence Basementioning
confidence: 99%
“…The small number of controlled systematic pharmacotherapy trials completed to date in general have failed to demonstrate the efficacy of tricyclic or serotonergic antidepressants for the acute treatment of child or adolescent major depression (Table 1). Two double-blind placebo-controlled studies in children (Puig-Antich et al, 1987;Geller et al, 1989) and five double-blind studies in adolescents (Kramer and Feiguine, 1981;Geller et al, 1990;Klein et al, 1992;Kutcher et al, 1994;Kye et al, 1996) with tricyclic antidepressants (amitriptyline, nortriptyline, imipramine, and desipramine) have not reported significant differences between placebo and TCAs (Thurber et al, 1995;Birmaher et al, 1996b). One double-blind controlled study in children reported a statistically significant but clinically small antidepressant effect with imipramine (Preskorn et al, 1987).…”
Section: Pharmacotherapy Of Child and Adolescent Mddmentioning
confidence: 99%